Multitemporal analysis of land use and occupation with a focus on agriculture, livestock and pebble extraction in the municipality of Ourém/PA, from 2016 to 2020 - Santos, Helane Cristina Aguiar; Caldeira, Carlos Rodrigo Tanajura; Costa, Yanna Karoline Santos da; Silva, Thamyres Marques da; Leite, Tabilla Verena da Silva; Lima, Valdeides Marques; Silva, Olavo Pimentel; Guerino, Rafaela da Silva; Martins, Jefferson dos Santos; Gonçalves, Marcos Augusto de Souza (Seven Editora, 2024)
The studies of the forms of use and coverage of the earth's surface are essential to provide subsidies for the environmental monitoring of a given area. The present work aimed to analyze the dynamics of land use and land cover in the municipality of Ourém/PA in the period from 2016 to 2020, generating representative information of the landscape dynamics, influenced by the physical and socioeconomic aspects inherent to this municipality. Land use and land cover classes were quantified and mapped with Google Earth Engine from  2016 to 2020. Data processing was performed using the ArcgisPro software to classify land use and land cover classes and to make maps. With the products generated, an image was selected for each year, in order to determine the areas for each thematic class of urban area, vegetation, agriculture and livestock, and pebble extraction, so that it was possible to quantify the class measurements. The results of each year were compared and a thematic map was prepared with the images selected to determine the use and occupation of the land in the municipality. The results revealed that the agriculture and pasture classes are predominant during the analyzed period, with a slight reduction in vegetation cover and a slight increase in the area of agriculture and pasture. Therefore, the identification and analysis of the classes of use and occupation provide both the understanding of these modes of use and the degradation to the environment, understanding the function of Man as a potential cause of this degradation. DOI:https://doi.org/10.56238/sevened2023.001-014